Intraocular lens power calculation for silicone oil-dependent eyes - Wang, Leyi; Wang, Xin; Yang, Xuepeng; Si, Yuanyuan; Wu, Jiayin; Cui, Yan (Frontiers in Medicine, 2023)
Background Silicone oil tamponade is widely used in vitreoretinal surgery. In some cases, silicone oil may not be extracted for a long time or even permanently and is referred to as silicone oil-dependent eyes. In this study, we aimed to deduce a theoretical formula for calculating intraocular lens power for silicone oil-dependent eyes and compare it with clinical findings. Methods A theoretical formula was deduced using strict geometric optical principles and the Gullstrand simplified eye model. The preoperative and postoperative refractive statuses of patients with silicone oil-dependent eyes who underwent intraocular lens implantation were studied (Group A, n = 13). To further test our derived theoretical formula, patients with silicone oil tamponade and first-stage intraocular lens implantation were included (Group B, n = 19). In total, 32 patients (32 eyes) were included in the study. Results In group A, the calculated intraocular lens power based on our formula was 24.96 ± 3.29 diopters (D), and the actual refraction of the patients was 24.02 ± 4.14D. In group B, the theoretical intraocular lens power was 23.10 ± 3.08D, and the clinical intraocular lens power was 22.84 ± 3.42D. There was no significant difference between the theoretical and clinical refractive powers, and the intraclass correlation coefficient was 0.771 for group A and 0.811 for group B (both p ≤ 0.001). The mean absolute error for silicone oil-dependent eyes of the formula was 1.66 ± 2.09D. After excluding data for two patients with a flat cornea (corneal refractive power < 42D), the mean absolute error decreased to 0.83 ± 0.62D. Conclusion A strong correlation between the theoretical and clinical intraocular lens powers was observed, and the formula we deduced can be used to calculate the intraocular lens power for silicone oil-dependent eyes. This formula will help clinicians select a more appropriate intraocular lens for patients with silicone oil-dependent eyes, especially when the corneal refractive power is ≥42D.